Knowledge Sharing Maturity in Telco Company Case Study: Territory Area X - Hidayat Akbar; Rizaldy Septa Amanda; Dana Indra Sensuse (Syntax Idea)
This study aims to determine the maturity level of knowledge sharing and recommendations to increase the maturity level in Telco organizations, especially in the territory area of PT ABC. This research uses KSM2 (Knowledge Sharing Maturity Model) to determine its maturity level into five stages, namely no KS level, project level, department level, organization level, and knowledge sharing at all levels. A mixed method was conducted in this study through literature review of papers and a survey of 100 respondents with 20 questions divided into three categories, Project level, Department level, and Organizational level. The result shows that the company in the territory area reaches an organizational level in the KSM2 model. The practice of knowledge sharing is good enough that takes place in the organization. but for feedback improvement, it has not been done well, there is no place to accommodate this yet. This research recommends some improvements to knowledge sharing in organizations. First, at the project level to improve proactive knowledge sharing with motivation. Second, at the department level to improve courage to express opinion in meetings. Third, at the organizational level must have routine knowledge sharing formally with a calendar of events. Besides the three points above, feedback and criticism to improve knowledge-sharing practice must be followed up to gain the next level in KS Maturity.